CREATIVE LEADERSHIP AFFECTING PERSONNEL MANAGEMENT OF SARASAS AFFILIATED SCHOOLS - Ponrachom , Janejira; Pechrpuang, Sopon (Journal of MCU Nakhondhat, 2023)
The purpose of this research were to study 1) the Creative Leadership of Administrators of Sarasas Affiliated Schools 2) the Personnel Management of Sarasas Affiliated Schools 3) the Creative Leadership Affecting Personnel Management of Sarasas Affiliated Schools. Population is teacher 7,869 person whom working for Sarasas Affiliated Schools, the sample were 367 person obtained by Stratified Random Sampling then use simple random sampling. The questionnaires was use to collect data and has reliability statistics is 0.97 of Cronbach’s Alpha for whole issue. The statistics used to analyze the data were mean, standard deviation and stepwise multiple regression analysis. The finding were 1) Creative Leadership of School Administrators in Sarasas Affiliated Schools Overall and each aspect was at a high level. ( = 3.7,SD=.69) Sorted from highest to lowest average as follows: Flexibility ( = 3.77,SD=0.68) vision ( = 3.73,SD=0.67) Imagination to create the future ( = 3.72,SD=0.69) and having trust ( = 3.70 SD=0.72) 2) Personnel management of Sarasas Affiliated Schools as a whole found that personnel management of Sarasas Affiliated Schools Overall and each aspect was at a high level. ( = 3.64 SD=0.72,) Sorted from the highest average to the lowest as follows: Personnel Development have the highest average. ( = 3.67,SD=0.71) Followed by recruitment and selection of personnel. ( = 3.66,SD=0.71) Evaluation of the performance of personnel ( = 3.65,SD=0.69) personnel maintenance ( = 3.62,SD=0.74) and manpower planning has the lowest average ( = 3.60,SD=0.71) 3) Creative Leadership Affects Personnel Management of Sarasas Affiliated Schools which all 4 variables can together predict the personnel management of Sarasas Affiliated Schools at 60.9 percent with statistical significance .05